Solid State bioconversion of oil palm biomass for ligninase enzyme production - Alam, Md. Zahangir; Mahmat, Mohd Erman; Muhammad, Nurdina (Taylor & Francis, 2005)
A laboratory-scale study of bioconversion of local lignocellulosic material, oil palm biomass (OPB) was conducted by evaluating the enzyme production through microbial treatment in solid state bioconversion (SSB). OPB in the form of empty fruit bunches (EFB) was used as a solid substrate and treated with the white-rot fungus, Phanerochaete chrysosporium, to produce ligninase. The results showed that the highest ligninase activity of 400.27U=liter was obtained at day 12 of fermentation. While the optimum study indicated the enzyme production of 1472.8U=liter with moisture content of 50%, 578.7U=liter with 10%v=w of inoculum size, and 721.8U=liter with co-substrate concentration of 1%(w=w) at days 9, 9 and 12 of fungal treatment, respectively. The parameters glucosamine and reducing sugar were observed to evaluate the growth and substrate utilization in the experiment.